Assessing the airborne survival of bacteria in populations of aerosol droplets with a novel technology. Issue 150 (31st January 2019) - Fernandez, Mara Otero; Thomas, Richard J.; Garton, Natalie J.; Hudson, Andrew; Haddrell, Allen; Reid, Jonathan P.
Abstract : The airborne transmission of infection relies on the ability of pathogens to survive aerosol transport as they transit between hosts. Understanding the parameters that determine the survival of airborne microorganisms is critical to mitigating the impact of disease outbreaks. Conventional techniques for investigating bioaerosol longevity in vitro have systemic limitations that prevent the accurate representation of conditions that these particles would experience in the natural environment. Here, we report a new approach that enables the robust study of bioaerosol survival as a function of relevant environmental conditions. The methodology uses droplet-on-demand technology for the generation of bioaerosol droplets (1 to greater than 100 per trial) with tailored chemical and biological composition. These arrays of droplets are captured in an electrodynamic trap and levitated within a controlled environmental chamber. Droplets are then deposited on a substrate after a desired levitation period (less than 5 s to greater than 24 h). The response of bacteria to aerosolization can subsequently be determined by counting colony forming units, 24 h after deposition. In a first study, droplets formed from a suspension of Escherichia coli MRE162 cells (10 8 ml −1 ) with initial radii of 27.8 ± 0.08 µm were created and levitated for extended periods of time at 30% relative humidity. The time-dependence of the survival rate was measured over a time period extending to 1 h. We demonstrate that this approach can enable direct studies at the interface between aerobiology, atmospheric chemistry and aerosol physics to identify the factors that may affect the survival of airborne pathogens with the aim of developing infection control strategies for public health and biodefence applications.